Analisis Kualitas Laporan Keuangan, Pengendalian Internal, dan Pemanfaatan Digital Accounting terhadap Keberlangsungan Usaha UMKM Kota Pekanbaru - Wulandari, Ika (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Many challenges exist in business, financial management is the most fundamental internal problem for MSMEs, which can undermine their sustainability. This research aims to analyze the relationship between the quality of financial reports, internal control, and the use of digital accounting on the sustainability of MSME businesses in Pekanbaru City. The research method used is a quantitative method with a survey approach by distributing questionnaires to MSME actors. The research sample used data from 100 respondents. The respondent criteria included MSME actors in the culinary sector in Pekanbaru City, active businesses, MSME actors registered with online services, operating for at least 1 year, having a physical store or permanent sales location, and a turnover of ≤ 2.5 billion per year. Data analysis using multiple linear regression was carried out for partial and simultaneous testing. The results of the research indicate that partially, the quality of financial reports has a positive and significant effect on the sustainability of MSME businesses. Internal control has a positive and significant effect on the sustainability of MSME businesses. Internal control has the largest regression coefficient (B = 0.464), so that mentoring can focus on SOPs, segregation of duties, and cash control. The use of digital accounting has a positive and significant impact on the sustainability of MSME businesses. The research results indicate that improving the quality of financial reports, optimizing internal controls, and utilizing digital accounting can improve the sustainability of MSME businesses. The adjusted R-squared result of the research is empirically proven at 45%. Meanwhile, the results of simultaneous testing for this study indicate that the quality of financial reports, internal controls, and the use of digital accounting have a positive and significant impact on the sustainability of MSME businesses in Pekanbaru City.